Sosialisasi Pola Asuh dalam Pembentukan Karakter Anak Bahagia dan Percaya Diri di Desa Cisitu - Rachmaniar, Ananda; Salsabila, Haudia Ulfa; Putri, Septianti Ananda (Ma'soem University, 2024)
This socialization activity is based on children who are cared for and live with grandmothers so that it affects the development of children's personality and character. The parenting style applied by grandmothers is different from the parenting style applied by their parents. This has a significant effect on the formation of children's personality and character. The purpose of this community service program is to provide understanding to parents and grandmothers about the importance of parenting in the formation of happy and confident children's characters in Cisitu Village. The method in this service activity is to use PAR (Participatory Action Research) which includes the stages of planning, implementation, results and evaluation. The results of the activity have been carried out well, parents gain knowledge on how to provide positive parenting to children and grandchildren because this is an effort to shape the character of children.